IV Międzynarodowa Konferencja Naukowa Uniwersalizm pracy ludzkiej Wyzwania dla edukacji (Szkoła - Zawód - Praca, 2020)
IV Międzynarodowa Konferencja Naukowa Uniwersalizm pracy ludzkiej Wyzwania dla edukacji.